Micromechanical Analysis of Flexible Low Density Open-Cell Foam with Unit Cell in Moulding Process Using Finite Element Method (Journal of Fiber Bioengineering and Informatics, 2013)
To investigate the compressive effects through microscopic features of flexible low-density open-cell PUfoam during moulding process, FE simulation of deformation based on a regular dodecahedron cell unitwith uniaxial compression behavior is undertaken to examine the mechanical properties of the verticalloading direction, and to facilitate the incorporation of solid PU material properties and variations incell geometry. By the use of a factorial design, the mean strut thickness of solid struts has a positivenon-linear effect on the maximum reaction force as compared against cell size with a negative non-lineareffect. The Young's modulus of solid polymers had a positive linear effect on the response while thePoisson's ratio had the least impact on the response. Development of a simplified cell unit can modelthe behavior of open-cell PU foam under uniaxial compression which is an effective way to understandthe mechanical behavior of foam during moulding process.
Keywords: Moulding; Mould Head; Numerical Simulation; Foam